Home for the holidays - Mumm, Debbie (Cumming, Iowa : Landauer Books, 1999)
Mummford and McFinn are lost but find their way to a small town where they learn about Christmas, Chanukah, and Kwanzaa.
"Children ages 4-8".
13 26
Keywords: Penguins -- Juvenile fiction; Christmas -- Juvenile fiction; Hanukkah -- Juvenile fiction; Kwanzaa -- Juvenile fiction